Immunoglobulin-producing cells in lymphatic tissues of germfree and conventional rabbits as detected by an immunofluorescence method - Stĕpánková, R; Kovárů, F (Folia microbiologica, 1985)
Lymphatic tissues of GF and CV rabbits were observed. No cells producing IgA and IgM antibodies were detected in appendix, sacculus rotundus, ileum terminale and thymus of GF rabbits. IgA cells were found in lymph nodes of GF rabbits.
Keywords: imunoglobulin A; Lymphoid Tissue; buňky produkující protilátky; imunoglobulin M; lymfoidní tkáň; Immunoglobulin G; cytoplazma; Cytoplasm; Immunoglobulin M; zvířata; Rabbits; imunoglobulin G; králíci; Immunoglobulin A; Germ-Free Life; gnotobiologické modely; Antibody-Producing Cells; Animals